2006
DOI: 10.1182/blood-2005-08-3452
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmin-cleaving enzyme is a soluble form of fibroblast activation protein

Abstract: Circulating antiplasmin-cleaving enzyme (APCE) has a role in fibrinolysis and appears structurally similar to fibroblast activation protein (FAP), a cell-surface proteinase that promotes invasiveness of certain epithelial cancers. To explore this potential relationship, we performed comparative structure/function analyses of the 2 enzymes. APCE from human plasma and recombinant FAP (rFAP) exhibited identical pH optima of 7.5, extinction coefficients (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 39 publications
2
146
0
Order By: Relevance
“…It shows the enzyme to have an active-site within a tube-like structure that courses through each monomeric half with apertures of 14 and 24 diameters at the ends of each tube. Although previously stated that FAP or its derivatives do not circulate in blood [6], we concluded that plasma APCE, which lacks the cytoplasmic tail and transmembrane sequence of FAP, may indeed result from FAP [7], possibly as a consequence of unidentified cell membrane "sheddase" activity as occurs with certain other membrane peptidases [8;9], or that it might be synthesized and secreted as a non-membrane-bound variant of FAP. To date Met-α 2 AP is the only definitive physiologic substrate identified for native APCE, and it is also cleaved by recombinant FAP [1;7].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…It shows the enzyme to have an active-site within a tube-like structure that courses through each monomeric half with apertures of 14 and 24 diameters at the ends of each tube. Although previously stated that FAP or its derivatives do not circulate in blood [6], we concluded that plasma APCE, which lacks the cytoplasmic tail and transmembrane sequence of FAP, may indeed result from FAP [7], possibly as a consequence of unidentified cell membrane "sheddase" activity as occurs with certain other membrane peptidases [8;9], or that it might be synthesized and secreted as a non-membrane-bound variant of FAP. To date Met-α 2 AP is the only definitive physiologic substrate identified for native APCE, and it is also cleaved by recombinant FAP [1;7].…”
Section: Introductionmentioning
confidence: 66%
“…Purification of APCE and expression and purification of recombinant FAP APCE was isolated from citrated human plasma (Sylvan Goldman Blood Institute, Oklahoma City, OK) by sequential chromatographic steps as previously described [7]. A soluble form of recombinant human FAP beginning at residue 35 was expressed by Pichia pastoris and purified from culture media as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble form of FAP, or antiplasmin cleaving enzyme (APCE), has been shown to cleave the long form of antiplasmin (Met-a 2 AP) to its more active form (Asn-a 2 AP). 39 We hypothesized that if treatment inhibited FAP endopeptidase activity, greater concentrations of Met-a 2 AP would be seen in the plasma with Val-boroPro treatment. Total a 2 AP was purified from patient plasma samples collected before starting treatment and after one week of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The active enzyme is a homodimer of two 97-kd subunits, and a soluble form of FAP␣ has also been reported (131,132). In contrast to DPP-4, FAP␣ typically is not expressed in normal tissues.…”
Section: )mentioning
confidence: 99%